A study on the factors that contribute to the baby dumping problem in Malaysia: a case study in Kebahagiaan Wanita dan Remaja (KEWAJA) / Farah Adilla Ab Rahman … [et al.] - Ab Rahman, Farah Adilla; Ghazali, Marni; Abdul Batau, Mohamed Fajil; Ayob, Nor Azira; Mohd Salleh, Norlina; Azhar, Siti Aisyah; Arifin, Suliana (Faculty of Administrative Science and Policy Studies, 2012)
Malaysia is now experiencing a huge social concern by a series of reports regarding on baby dumping which becoming one of the headlines in the media nowadays. The babies were left to die in manner such as leaving the newborn in a dumpster, garbage bin, sewage tank, on the signboard and include outlets at isolated places such as at abandoned shop-houses and etc. The purpose of this study is to examine the relationship between factors which contribute on baby dumping and also to identify the most influential factor that contribute towards baby dumping problem. The research was conducted in one of the non-governmental organization in this country that is known as Kebahagiaan Wanita dan Remaja (KEWAJA). The findings revealed that there are significant relationships between four factors which are family problem, premarital sex intercourse, lack of religious knowledge, and mass media influence that contribute towards baby dumping problem. However, there is one factor that did not have significant relationship to baby dumping which is lack of sexual knowledge. Furthermore, through the findings, the researchers had identified the most influential factor that contribute towards the problem of baby dumping which is family problem while the least factor that contribute is lack of religious knowledge.